PENGARUH GAJI DAN KARIER TERHADAP KINERJA KARYAWAN PT. ARMA ANUGERAH ABADI MEDAN - rizal, syaf (Akuntansi Prima, 2023)
This study aims to examine and analyze the effect of salary and career on the performance of employees of PT. Arma Anugerah Abadi Medan. This research was conducted using a quantitative approach, namely hypothesis testing. The data analysis method used is multiple linear regression method. The population used is all employees of PT. Arma Anugerah Abadi Medan as many as 30 employees of PT. Arma Anugerah Abadi Garu 2 Unit Medan, sampling using the census method. The results obtained indicate that the two variables proposed in this study have a significant influence on employee performance.